The Impact of the Digital Economy on Economic Empowerment Models for Muslim Youth in Indonesia - Cahaya Rembulan; Ibnu Roghidul Maghfur; Mahrus Alwi Hasan Siregar; Moh Ali Jakfar; Sofiatus Solehah (Mahkota Science Publishers, 2025)
This study aims to challenge the dominant narrative, identify structural and cultural issues that are often hidden, and offer middle-ground solutions rooted in the values of social justice, collective empowerment, and innovation based on religion and technology in Indonesia. This study employs a library research approach, utilising academic literature, research reports, and policy documents to develop a comprehensive understanding of the impact of the digital economy on the economic empowerment of Muslim youth in Indonesia. The results show that the digital economy has brought about a quantum leap in the empowerment of Indonesian Muslim youth, accelerating their access to and participation in various business and innovation sectors, while encouraging the emergence of a new, more progressive and independent identity. However, behind these opportunities lie serious challenges in including a dilemma between digital business efficiency and consistency with Sharia principles, as well as the fragmentation of religious authority due to the dominance of influencer narratives in the digital space. Therefore, the economic empowerment of Muslim youth through digital technology will only be meaningful if it is accompanied by the strengthening of critical literacy, ethical integrity, and collaboration among stakeholders to ensure that every digital business innovation and practice not only pursues growth and virality, but truly supports justice, sustainability, and Sharia objectives as the primary foundation for the progress of the ummah in this era of transformation.